Administration of vitamin D by injection or drinking water alters serum 25-hydroxycholecalciferol concentrations of nursery pigs - Young Dal Jang; Jingyun Ma; Ning Lu; Jina Lim; H. James Monegue; Robert L. Stuart; Merlin D. Lindemann (Asian-Australasian Journal of Animal Sciences, 2018)
Objective Two experiments were conducted to evaluate vitamin D3 administration to nursery pigs by injection or in drinking water on serum 25-hydroxycholecalciferol (25-OHD3) concentrations. Methods At weaning, 51 pigs (27 and 24 pigs in experiments 1 and 2, respectively) were allotted to vitamin D3 treatments. Treatments in experiment 1 were: i) control (CON), no vitamin administration beyond that in the diet, ii) intramuscular (IM) injection of 40,000 IU of vitamin D3 at weaning, and iii) water administration, 5,493 IU of vitamin D3/L drinking water for 14 d postweaning. Treatments in experiment 2 were: i) control (CON), no vitamin administration, and ii) water administration, 92 IU of d-α-tocopherol and 5,493 IU of vitamin D3/L drinking water for 28 d postweaning. The lightest 2 pigs within each pen were IM injected with an additional 1,000 IU of d-α-tocopherol, 100,000 IU of retinyl palmitate, and 100,000 IU of vitamin D3. Results In both experiments, serum 25-OHD3 was changed after vitamin D3 administration (p<0.05). In experiment 1, injection and water groups had greater values than CON group through d 35 and 21 post-administration, respectively (p<0.05). In experiment 2, serum values peaked at d 3 post-administration in the injection groups regardless of water treatments (p<0.05) whereas CON and water-only groups had peaks at d 14 and 28 post-administration, respectively (p<0.05). Even though the injection groups had greater serum 25-OHD3 concentrations than the non-injection groups through d 7 post-administration regardless of water treatments (p<0.05), the water-only group had greater values than the injection-only group from d 21 post-administration onward (p<0.05). Conclusion Serum 25-OHD3 concentrations in pigs increased either by vitamin D3 injection or drinking water administration. Although a single vitamin D3 injection enhanced serum 25-OHD3 concentrations greater than water administration in the initial period post-administration, a continuous supply of vitamin D3 via drinking water could maintain higher serum values than the single injection.